1996
DOI: 10.5547/issn0195-6574-ej-vol17-no1-3
|View full text |Cite
|
Sign up to set email alerts
|

The Total Cost and Measured Performance of Utility-Sponsored Energy Efficiency Programs

Abstract: By examining the actual performance of conservation or demand-side management (DSM) programs for ten utilities, Joskow and Marron (1992) have made an important contribution to policy discussions about the wisdom of relying on utilities to improve customer energy efficiency. We use Joskow and Marrons method to analyze twenty utility commercial lighting programs and, like Joskow and Marron, find wide variations in industry reporting practices and savings evaluation methods. We extend the method by systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…These modifications revealed that reported utility DSM spending may be more accurate than Loughran and Kulick claimed, a finding that supports Parfomak and Lave's original conclusions. Qualitative studies confirm the findings made by all three sets of authors that DSM efforts are cost‐effective and have significant potential to decrease electricity prices (Eto et al, 1996, 2000; Nadel, 1992; Nadel & Geller, 1996).…”
Section: Introductionsupporting
confidence: 76%
“…These modifications revealed that reported utility DSM spending may be more accurate than Loughran and Kulick claimed, a finding that supports Parfomak and Lave's original conclusions. Qualitative studies confirm the findings made by all three sets of authors that DSM efforts are cost‐effective and have significant potential to decrease electricity prices (Eto et al, 1996, 2000; Nadel, 1992; Nadel & Geller, 1996).…”
Section: Introductionsupporting
confidence: 76%
“…6 Recall that this is one criticism associated with the PRISM methodology since the use of long-term weather conditions precludes daily analysis. 7 Entergy for example has 11 billing cycles throughout Louisiana.…”
Section: Model Constructionmentioning
confidence: 99%
“…Industrial and commercial facilities have evolved standard protocol for evaluating energy conservation programs, primarily because of the large capital expenses involved, but residential programs tend to be subject to less rigorous criteria and performance metrics. For a review of program assessments in commercial facilities, see [7,8]; for residential programs, [15]; for weatherization, [2,4,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a review of 40 large-scale commercial sector energy efficiency programs implemented during the early 1990s found that they saved electricity at an average cost of $0.032 per kWh, well below the cost of supplying electricity (Eto et al,1996). This study relied on post-program evaluations of energy savings, and included all utility costs as well as customer costs in its analysis.…”
Section: Box 112 the Evaluation Of Energy-efficiency Programs In Camentioning
confidence: 99%